Lobsters : Biology, Management, Aquaculture and Fisheries - Phillips, Bruce F. (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
This expanded and fully updated Second Edition of the most comprehensive and successful book on lobsters, comprises contributions from many of the world's experts, each providing core information for all those working in lobster biology, fisheries research and management and lobster aquaculture. Under the editorship of Bruce Phillips, the Second Edition of Lobsters: Biology, Management, Fisheries and Aquaculture delivers exhaustive coverage of these fascinating creatures, stretching from growth and development to management and conservation. A number of chapters from the First.
3.2.3 Displacement and integration of released lobsters3.2.4 Habitat and predator change; 3.3 Economic and policy issues; 3.3.1 Economic feasibility; 3.3.2 Optimal management of harvests with enhancement; 3.3.3 Ownership, policy and risk; 3.4 Case studies; 3.4.1 Clawed lobster restocking; 3.4.2 Range extension of American lobster to Europe; 3.4.3 Improving yield in Southern rock lobster: translocating low quality adults; 3.5 Conclusions; References; Chapter 4: The Impact of Climate Change on Exploited Lobster Stocks; 4.1 Introduction; 4.2 Case studies.
Includes bibliographical references and index.
Print version record.
Keywords: Lobsters; SCIENCE -- Life Sciences -- Zoology -- General; Lobsters; Lobsters; Electronic books; Electronic books